EVALUATION QUALITY OF LIFE OF TYPE 2 DIABETIC PATIENTS WITH ORAL ANTIDIABETIC THERAPY AT AMBULATORY CLINIC IN RSUP DR. SARDJITO - Rafika Mutia Sari; Jarir At Thobari; Tri Murti Andayani (Faculty of Pharmacy, Universitas Gadjah Mada)
Type 2 Diabetes Mellitus is a chronic disease which can’t be healed totally. Therefore type 2 DM will affect the Health Related Quality of Life (HRQOL). The purpose of this study was to determinate the QOL of type 2 DM patients based on patient’s characteristics, drug groups, and therapy pattern (single versus combination therapy). This study was conducted in RSUP Dr. Sardjito Yogyakarta. This study is an analytical research with cross sectional design. Data collection was done by interview and review of patient’s medical records. Research’s subjects are ambulatory patient with type 2 DM who are threated with oral antidiabetic(s) and willing to fill the questionnaire. Total 227 total patients were included in this study. Quality of life was measured by Diabetes Quality of Life Clinical Trial Questionnaire (DQLCTQ). The analysis showed that gender, age, duration of DM, educational level, marital status and occupation affect the QOL. Patient taking metformin had 67.9 score, 67.7 for patient with acarbose therapy and patient taking sulfonylurea 67.6 score. Those differences were not significant (ANOVA test, p = 0.298). Patients taking single antidiabetic agent had 70.6, whereas those taking combination therapy had 67.6 score. Independent sample t‐test showed that those score have significant difference (p = 0.002). Linear regression analysis with enter method showed that QOL’s difference between single and combination therapy groups did affected by patient’s characteristics (p=0.049). Keywords : type 2 DM, ADO therapy, quality of life, DQLCTQ